Huge Interatrial Septal Aneurysm: A Coincidental but Rather Fatal Finding. (5th January 2011) - Tzimas, Petros; Papadopoulos, Georgios
Abstract : We report the case of a patient with a huge interatrial septal aneurysm as an intraoperative coincidental finding that led to a fatal outcome. The patient was admitted to our hospital in order to undergo elective coronary artery bypass grafting because he suffered from severe coronary artery disease. We intraoperatively diagnosed by transesophageal echocardiography a huge interatrial septal aneurysm mimicking a right atrial tumor. The aneurysm was initially resected and then coronary artery bypass grafting was successfully performed but the patient never achieved a successful separation from cardiopulmonary bypass probably because of massive embolic events.